Aerial census of reindeer in Taimyr, Russia, 2003 - Andrey Petrov; Leonid Kolpashchikov; John DeGroote; Nikolay Golosov (Arctic Data Center, 2020)
The dataset is a part of a comprehensive information system that provides insight into the historical relationship between humans, climate, environment, and reindeer in Taimyr, Russia. This dataset is a product of digitization and reanalysis of historical aerial observational data collected in 1969 by the researchers from the Extreme North Agriculture Research Institute. The data contain spatial data representation and descriptions based on the approximate flight paths undertaken in July of 1969 reconstructed from the unpublished aerial census report and data log. The Taimyr Reindeer Migration Reanalysis (TAMARA) project is an integral part of the worldwide network of reindeer observation programs.